Selection of solvent for extraction of antioxidant components from Cynanchum auriculatum, Cynanchum bungei, and Cynanchum wilfordii roots. Issue 4 (20th February 2019) - Wu, Cheng‐Dong; Zhang, Ming; He, Ming‐Tao; Gu, Min‐Feng; Lin, Mei; Zhang, Gen
Abstract: In east Asia, "Baishouwu" has been used as an herbal drug and functional dietary supplement for hundreds of years. Actually, "Baishouwu" is the common name of the roots of Cynanchum auriculatum, Cynanchum bungei, and Cynanchum wilfordii . In the present study, roots of these three specie were extracted and then fractionated using petroleum ether (PE), dichloromethane (DCM), ethyl acetate (EA), and water. DPPH scavenging experiments revealed high antioxidant activity of DCM and EA fractions of C. bungei and the EA fraction of C. wilfordii . Treatments with these three fractions significantly reduced malondialdehyde content in heat‐stressed Daphnia magna, validating in vivo antioxidant activity. Gas chromatography–mass spectrometer (GC‐MS) analyses demonstrated that the chemical components of fractions extracted from C. bungei, C. bungei, and C. wilfordii were different. Further determination of total phenol and total flavonoids contents showed that DCM and EA fractions of C. bungei and EA fraction of C. wilfordii had much higher contents of total phenol and total flavonoids, which might be the reason to explain their strong antioxidant activity. Overall, the present study suggested that these three plants have different chemical components and biological activities. They could not be used as the same drug. Abstract : Dichloromethane and ethyl acetate fractions of Cynanchum bungei and the ethyl acetate fraction of Cynanchum wilfordii revealed antioxidant activity. No antioxidant activity was observed for all extracts from Cynanchum auriculatum .